Clinical Indications Of Navaka Guggulu An Experiential And Scientific View - Shripathi , Acharya G; Acharya, Rajeshwari S (International Research Journal of Ayurveda & Yoga, 2021)
Guggulu (Commiphora wightii Arn. Bhandari) is the major constituent in Navaka Guggulu, a well-known polyherbal preparation. Medoroga (hyperlipidemia), Sthaulya (obesity), and other Kaphaja rogas benefit from it. Fresh (Naveena) Guggulu is said to have a Brimhana (body mass growing) impact, whereas aged (Purana) Guggulu is said to have an Atilekhana (body mass decreasing) effect (scrapping). The current research discusses the clinical indications of Navaka guggulu from a scientific and practical standpoint. The pungent flavor, light and dry qualities, and dominant medications Ushna Veerya and KatuVipaka in Navaka Guggulu have all the properties to break down the etiology of hyperlipidemia. These qualities are beneficial in lowering the lipid profile. The present paper highlights about the clinical indications of Navaka guggulu in a scientific and experiential view.